The incidence of wound infection and dehiscence following childbirth-related perineal trauma: A systematic review of the evidence. (September 2019) - Jones, Kathy; Webb, Sara; Manresa, Margarita; Hodgetts-Morton, Victoria; Morris, R.Katie
Abstract: Objectives: Approximately 85% of vaginal births are affected by childbirth related perineal trauma, either spontaneously or as a result of an episiotomy. Perineal infection in the postnatal period is associated with wound dehiscence, granulation tissue formation, dyspareunia and pelvic floor dysfunction. Despite leading to long-term physical and psychological problems, the incidence of infection continues to remain unclear. This review is designed to determine the incidence of childbirth related perineal wound infection and dehiscence. Study design: A systematic review to determine the incidence of wound infection and dehiscence associated with childbirth-related perineal trauma. Medline, Embase and Cinahl databases were searched from inception to September 2018 using MeSH, textwords and appropriate word variants to ensure capturing all relevant studies. No restrictions were placed on birth mode, degree of trauma, parity, country or language. Results: 23 studies were included (11 cohort, 2 case control and 10 reporting incidence). Reported incidence of childbirth-related perineal trauma wound infection ranged from 0.1%–23.6% and wound dehiscence from 0.21%–24.6%. Quality assessment of included studies exposed inadequacies in several methodological areas. There was great clinical heterogeneity amongst the studies, particularly regarding perineal wound infection definition and confirmation, making effective synthesis of the data almost impossible. Conclusion: Despite the known high occurrence of perineal trauma during childbirth and associated long-term morbidities, this review clearly demonstrates the true incidence of infection remains largely unknown. This can be attributed to multiple factors including lack of high level evidence around understanding 'normal' perineal wound healing, absence of a core outcome set for childbirth-related perineal trauma and that women present to a variety of healthcare settings for treatment. It is vital that a validated childbirth-related perineal trauma diagnostic tool and core outcome set are developed for use in future studies to facilitate improved diagnosis and treatment and reduce long term morbidities of women affected by childbirth-related perineal trauma wound infection and dehiscence.